The Impact of Information Acquisition Costs on Managerial Investment Choices - Ardi Armen; Taufan Herjanto (LPPM STIE Kasih Bangsa, 2024)
This research examines the impact of information acquisition costs on managerial investment choices, focusing on expenses to gathering, processing, and analyzing data necessary for informed decision-making in investments. The review synthesizes findings from various studies to highlight how these costs influence managerial behaviors, investment strategies, and decision-making processes. Key insights include the trade-offs managers face between the costs of acquiring information and the potential benefits of improved decision quality. Technological advancements and organizational culture are identified as critical factors shaping strategies to mitigate information acquisition costs. Contextual variations, such as market volatility and regulatory environments, further influence the strategies firms adopt in managing these costs